KONSEP PENDIDIKAN KELUARGA DALAM AL-QUR’AN - Ilyas, Muhammad (Tawazun: Jurnal Pendidikan Islam, 2018)
Education will work effectively and intact if it involves three institutions: family, school, and society. Education will not work well if it ignores one of three institutions, namely family, school, and society. Among all three, the family environment has been the strongest influence on human development. This article discusses the concept of family education in Al-Qur'?n with the study of the thematic interpretations of the verses related to family education. The approach used in this research is library research.